2018
DOI: 10.1259/bjr.20180334
|View full text |Cite
|
Sign up to set email alerts
|

Identifying epidermal growth factor receptor mutation status in patients with lung adenocarcinoma by three-dimensional convolutional neural networks

Abstract: The CNN showed some diagnostic power and its performance could be further improved by increasing the training set, optimizing the network structure and training strategy. Medical image based CNN has the potential to reflect spatial heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Although Liu et al [27] and Rizzo et al [29] achieved relatively higher AUC scores of 0.709 and 0.82, respectively, their studies did not include independent testing groups which are essential to establishing the robustness of predictive models. Xiong et al [23] and Li et al [19] showed impressive results by using 3D deep learning model trained from scratch and achieved AUC scores of 0.776 and 0.809, respectively. Our model was trained and validated using the same patient cohort as Li's work [19] and, in an independent testing group, achieved a higher AUC score than any previously published study in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Liu et al [27] and Rizzo et al [29] achieved relatively higher AUC scores of 0.709 and 0.82, respectively, their studies did not include independent testing groups which are essential to establishing the robustness of predictive models. Xiong et al [23] and Li et al [19] showed impressive results by using 3D deep learning model trained from scratch and achieved AUC scores of 0.776 and 0.809, respectively. Our model was trained and validated using the same patient cohort as Li's work [19] and, in an independent testing group, achieved a higher AUC score than any previously published study in this area.…”
Section: Discussionmentioning
confidence: 99%
“…CT images from 1,010 consecutive patients with known EGFR status were retrospectively collected from 2013 to 2017, including 510 patients whose tumors were EGFR-mutated and 500 who were wild type [23]. Details are shown in TABLE 1.…”
Section: A Clinical Datamentioning
confidence: 99%
“…This approach is a non-invasive and easy-toimplement deep learning method. Other studies (27)(28)(29) also show that deep learning models can identify gene mutations in lung cancer.…”
Section: Original Articlementioning
confidence: 94%
“…4 Development and validation of novel technologies to longitudinally assess tumour dynamics relevant to targeted therapies With active anticipation of targeted therapy resistance emergence, advances in radiological assessment and 'liquid biopsy' (Bodei et al 2016, Khan et al 2016) may foster new approaches to monitor for early signs of not only the dichotomous outcomes of tumour relapse, but quantitative closeto-real-time changes in tumour sub-clone genetics, metabolic phenotypes or other plastic effects. In the realm of image analysis, radiomics and convolutional neural networks have both been utilised to predict with favourable degrees of accuracy the presence of targetable mutations on CT imaging (Xiong et al 2018, Jia et al 2019 and also grade in pancreatic NEN using CT imaging (Luo et al 2020), suggesting that they could function not only as part of diagnostic solutions (direct targeted genetic sequencing) but also as follow-up (reduction of likelihood of mutation presence, or emergence of another) -this will require an expanded cross-institutional collaboration to develop such models. Circulating tumour cells or transcripts may also be aspects of real-time monitoring for waxing/ waning therapy efficacy.…”
Section: Incorporate Genetics As Part Of a Multi-omics Perspective Wimentioning
confidence: 99%